Eating Disorders in Late-life - Luca, Antonina (Aging Dis, 2014)
Eating disorders are a heterogeneous group of complex psychiatric disorders characterized by abnormal eating behaviours that lead to a high rate of morbidity, or even death, if underestimated and untreated. The main disorders enlisted in the chapter of the Diagnostic and Statistic Manual of Mental Disorders-5 dedicated to “Feeding and Eating Disorders” are: anorexia nervosa, bulimia nervosa and binge eating disorder. Even though these abnormal behaviours are mostly diagnosed during childhood, interesting cases of late-life eating disorders have been reported in literature. In this review, these eating disorders are discussed, with particular attention to the diagnosis and management of those cases occurring in late-life.